KLASIFIKASI TALAQ DAN KONSEKUENSI HUKUMNYA DALAM PERSPEKTIF HUKUM ISLAM: KAJIAN NORMATIF TERHADAP BENTUK DAN AKIBAT PERCERAIAN - Ade Sultan Muhammad; Ika Yuliana Susilawati (Sekolah Tinggi Islam Syariah (STIS) Al-Ittihad Bima, 2026)
Talaq is one of the divorce mechanisms in Islamic law that encompasses various classifications and legal consequences. However, public understanding of the different types of talaq and their legal implications remains limited, often leading to misunderstandings regarding the rights and obligations arising after divorce. This study aims to examine the classifications of talaq in Islamic law and analyze the legal consequences associated with each type. The research employs a normative legal research method using a conceptual approach and library research. The data were collected from the Qur'an, Hadith, classical Islamic jurisprudential literature, books, and relevant scholarly publications on Islamic family law. The findings reveal that talaq can be classified based on the right of reconciliation, the timing of its pronouncement, the wording used, the number of pronouncements, and special forms such as khulu', talaq tafwidh, talaq ta'liq, li'an, ila', and zhihar. Each type of talaq carries distinct legal implications concerning reconciliation rights, maintenance during the waiting period (*iddah*), marital status, and the possibility of remarriage. Therefore, a comprehensive understanding of the classifications of talaq and their legal consequences is essential to ensure legal certainty and protect the rights of all parties in accordance with the principles of Islamic law.